Cryophysiology of coral microfragments: effects of chilling and cryoprotectant toxicity - Lager, Claire V. A.; Perry, Riley; Daly, Jonathan; Page, Christopher; Mizobe, Mindy; Bouwmeester, Jessica; Consiglio, Anthony N.; Carter, Jake; Powell-Palm, Matthew J.; Hagedorn, Mary (PeerJ, 2024)
Coral reefs are being degraded at alarming rates and decisive intervention actions are urgently needed. One such intervention is coral cryopreservation. Although the cryopreservation of coral sperm and larvae has been achieved, preservation of coral fragments including both its tissue and skeleton, has not. The overarching aim of this study was to understand and assess the physiological stressors that might underlie coral fragment cryopreservation, understand the long-term consequences of these exposures to continued growth, and develop a health metrics scale for future research. Therefore, we assessed small fragments ( 1 cm2) from the Hawaiian coral, Porites compressa, examining: (1) chill sensitivity; (2) chemical sensitivity to complex cryoprotectants; (3) methods to safely remove algal symbionts of coral for cryopreservation; (4) continued growth over time of coral fragments exposed to chilling and cryoprotectants; and (5) assessment of health and viability of coral fragments post the applied treatments. Corals were able to withstand chilling to 0 °C for 1 min and after 2 weeks were not significantly different from the live controls, whereas, corals exposed to complex cryoprotectants needed 3 weeks of recovery. Most importantly, it appears that once the coral fragments had surpassed this initial recovery, there was no difference in subsequent growth. Technological advances in cryo-technology promise to support successful coral fragment cryopreservation soon, and its success could help secure much of the genetic and biodiversity of reefs in the next decade.
Keywords: Porites compressa; Confocal imaging; Green fluorescent protein; Microfragment